Preprocedural P2Y12 inhibition and decrease in platelet count following transcatheter aortic valve replacement. Issue 6 (6th May 2019) - Ibrahim, Homam; Vapheas, Eleonora; Shah, Binita; AlKhalil, Ahmad; Querijero, Michael; Jilaihawi, Hasan; Neuburger, Peter; Staniloae, Cezar; Williams, Mathew R.
Abstract: Background: Thrombocytopenia after transcatheter aortic valve replacement (TAVR) is associated with adverse clinical outcomes. Whether preprocedural P2Y12 inhibition prevents postprocedural thrombocytopenia is uncertain. Methods: This retrospective analysis identified consecutive patients ( n  = 266) undergoing TAVR between November 2016 and July 2017. Preprocedure clopidogrel load ≥300 mg or maintenance P2Y12 inhibitor therapy defined preprocedural P2Y12 inhibition. Patients who did not consent for the registry ( n  = 8), with baseline severe thrombocytopenia (<90 × 10 3  platelets/μL; n  = 14), or without baseline platelet count ( n  = 4) were excluded. The primary outcome was proportion of patients who developed >20% decrease in platelet count from baseline to day 1 post‐TAVR. Results: Patients with ( n  = 134) versus without ( n  = 106) preprocedural P2Y12 inhibition had no differences in platelet count at baseline. Patients with preprocedural P2Y12 inhibition had a significantly lower proportion of the primary outcome (34.3% vs. 57.5%, p  = .001) and a lower absolute decrease in platelet count (32.8 × 10 3 vs. 45.8 × 10 3  platelet/μL, p  = .01). Of patients without baseline thrombocytopenia ( n  = 198), a numerically lower rate of patients with versus without preprocedural P2Y12 inhibition developed thrombocytopenia on day 1 post‐TAVR (25.5% vs. 36.4%, p  = .1). Conclusion: Patients who received preprocedural P2Y12 inhibition prior to TAVR were less likely to demonstrate a decrease in platelet count after TAVR. Prospective studies to further understand the clinical implication of these findings are warranted.